Precursor of manganese-based positive electrode material as well as preparation method and application of precursor
The precursor of spindle-shaped manganese-based positive electrode material was prepared by co-precipitation reaction, which solved the problems of poor structural stability and poor electrochemical performance of manganese-based positive electrode material, and achieved improvement in the specific capacity and cycle stability of lithium-ion batteries.
Patent Information
- Application Number
- CN202510137712.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-15
AI Technical Summary
Manganese-based positive electrode materials have problems such as poor structural stability and poor electrochemical performance, resulting in low specific capacity and poor circulation performance of lithium-ion batteries.
The precursor of the manganese-based positive electrode material was prepared by using the co-precipitation reaction method, using carbonate, bicarbonate and hydroxide as the composite precipitation agent, and alcohol amine as the crystal guide agent, and the reaction conditions were controlled to prepare a spindle-shaped precursor.
The prepared manganese-based cathode material has a more stable structure and excellent electrochemical properties, which improves the specific capacity and cycle stability of lithium-ion batteries.
Smart Images

Figure CN119822425A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a precursor of a manganese-based positive electrode material and a preparation method and application thereof. Background Art
[0002] The new energy industry has an increasingly urgent demand for lithium-ion batteries, especially high-energy-density lithium batteries. Manganese-based cathode materials have attracted widespread attention due to their advantages in specific energy density and cost, and are considered to be one of the most promising cathode materials for high-energy-density lithium-ion batteries.
[0003] However, manganese-based cathode materials have problems such as poor structural stability and poor electrochemical performance, which leads to low specific capacity and poor cycle performance of the battery. By regulating the morphology and structure of the manganese-based cathode material precursor, the structural stability of the lithium-rich manganese-based cathode material can be improved, thereby improving its electrochemical performance.
[0004] At present, the precursors of manganese-based positive electrode materials are generally prepared by co-precipitation. The primary particles of the precursors of manganese-based positive electrode materials prepared by the co-precipitation method are mostly lamellar or thin flakes. The manganese-based positive electrode materials prepared by the co-precipitation method are mostly spherical or quasi-spherical secondary particles formed by the aggregation of primary particles. The manganese-based positive electrode materials prepared with this morphology are structurally unstable, which leads to poor electrochemical performance of the battery. Summary of the invention
[0005] In view of the above problems, the object of the present invention is to provide a precursor of a manganese-based positive electrode material and a preparation method and application thereof.
[0006] In a first aspect, the present invention provides a precursor of a manganese-based positive electrode material, wherein the chemical formula of the precursor of the manganese-based positive electrode material is Ni x Mn y Co 1-x-y (OH)2, wherein: 0.65≤y≤0.9, 0<x≤0.3; its primary particles are spindle-shaped particles.
[0007] Preferably, the secondary particles of the precursor of the manganese-based positive electrode material are branch-shaped particles composed of spindle-shaped particles interlaced and interconnected.
[0008] Preferably, the D50 of the precursor of the manganese-based positive electrode material is 2-5 μm.
[0009] In the second aspect, the present invention provides a method for preparing a precursor of a manganese-based positive electrode material, which is a co-precipitation reaction method, in which at least one of carbonate and bicarbonate and hydroxide are used as composite precipitants, and alcohol amine is used as a crystal directing agent; the composite precipitant solution, alcohol amine solution, metal salt mixed solution and complexing agent solution are subjected to a co-precipitation reaction to prepare a precursor of the manganese-based positive electrode material.
[0010] Preferably, the hydroxide is one or both of sodium hydroxide and potassium hydroxide; the carbonate is one or both of sodium carbonate and potassium carbonate; and the bicarbonate is one or both of sodium bicarbonate and potassium bicarbonate.
[0011] Preferably, in the composite precipitant, the mass ratio of carbonate and bicarbonate to the mass ratio of hydroxide is 1:(20-100); and the concentration of the composite precipitant in the composite precipitant solution is 50-300 g / L.
[0012] Preferably, the alcoholamine is one or more of monoethanolamine, diethanolamine and triethanolamine; and the concentration of the alcoholamine solution is 0.1-5 g / L.
[0013] Preferably, the metal salt mixed solution is configured according to the metal elements and the ratio of the metal elements required in the chemical formula of the precursor of the manganese-based positive electrode material; the concentration of the metal salt in the metal salt mixed solution is 85-115 g / L.
[0014] Preferably, the complexing agent is one or more of ammonia water, ammonium bicarbonate, ammonium sulfate or ammonium oxalate solution; the concentration of the complexing agent solution is 5-40 g / L.
[0015] Preferably, during the coprecipitation reaction, the pH of the reaction system is controlled to be 10.0-11.5.
[0016] Preferably, the stirring speed of the coprecipitation reaction is 500-1000 rpm.
[0017] Preferably, the coprecipitation reaction temperature is 45-60°C.
[0018] Preferably, a method for preparing a precursor of a manganese-based positive electrode material specifically comprises the following steps: (1) Mix water, precipitant, complexing agent and alcohol amine to prepare the reaction base liquid; (2) A composite precipitant solution, an alcohol amine solution, a metal salt mixed solution, and a complexing agent solution are simultaneously introduced into the reaction base liquid to carry out a co-precipitation reaction; when the precipitate reaches a target particle size, a precursor of a manganese-based positive electrode material is obtained.
[0019] Preferably, in step (1), the precipitant is one or both of sodium hydroxide and potassium hydroxide, and the concentration of the precipitant in the reaction base liquid is 50-300 g / L.
[0020] Preferably, in step (1), the concentration of the alcoholamine in the reaction base solution is 0.1-2 g / L.
[0021] Preferably, in step (1), the concentration of the complexing agent in the reaction base solution is 1-10 g / L.
[0022] Preferably, in step (1), the pH of the reaction base solution is 11-13.
[0023] Preferably, in step (1), the complexing agent is one or more of ammonia water, ammonium bicarbonate, ammonium sulfate or ammonium oxalate solution.
[0024] Preferably, in step (2), the target particle size is 2-5 μm.
[0025] Preferably, in the step (2), the coprecipitation reaction further includes sequentially performing filtration, washing and drying.
[0026] Preferably, the drying temperature is 80-130°C.
[0027] In a third aspect, the present invention provides a manganese-based positive electrode material prepared by sintering a precursor of the aforementioned manganese-based positive electrode material with mixed lithium.
[0028] Preferably, the manganese-based positive electrode material is a quasi-single crystal manganese-based positive electrode material.
[0029] In a fourth aspect, the present invention provides a method for preparing a manganese-based positive electrode material, comprising the following steps: The precursor of the manganese-based positive electrode material is mixed with a lithium source and then calcined in an oxygen-containing atmosphere to obtain the manganese-based positive electrode material.
[0030] Preferably, the lithium source is one or both of lithium carbonate and lithium oxide, and the molar ratio of the precursor of the manganese-based positive electrode material to the lithium in the lithium source is 1:(1.3-1.5).
[0031] Preferably, the oxygen-containing atmosphere is an oxygen atmosphere or an air atmosphere.
[0032] Preferably, the calcination temperature is 850-1000° C., and the calcination time is not less than 8 hours.
[0033] In a fifth aspect, the present invention provides a lithium-ion battery comprising the aforementioned manganese-based positive electrode material.
[0034] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: (1) The primary particles of the precursor of the manganese-based positive electrode material in the present invention are spindle-shaped particles. The spindle-shaped particles help to form a manganese-based positive electrode material with a more stable structure during the calcination process, thereby effectively improving the specific capacity and cycle stability of the battery.
[0035] (2) The primary particles of the precursor of the manganese-based positive electrode material in the present invention are spindle-shaped, and the spindle-shaped primary particles are cross-connected to form a precursor with a special branch structure. The branch-like structure can be used to prepare a manganese-based positive electrode material with a relatively uniform morphology through calcination, thereby improving the electrochemical performance of the positive electrode material.
[0036] (3) The precursor of the manganese-based positive electrode material in the present invention can be used to efficiently prepare a manganese-based positive electrode material with a relatively uniform single-crystal morphology. The single-crystal-like particles effectively shorten the lithium ion diffusion path during the charge and discharge process, improve the charge transfer efficiency, and thus improve the discharge specific capacity of the manganese-based positive electrode material. At the same time, due to the low surface energy and high chemical stability of the single crystal structure, the high cycle performance of the lithium-ion battery is maintained.
[0037] (4) In the preparation method of the precursor of the present invention, the mass ratio of hydroxide to carbonate or bicarbonate in the composite precipitant is controlled, and an alcohol amine is added as a crystal directing agent to control the growth mode of the crystal, thereby preparing a precursor of a spindle-shaped manganese-based positive electrode material, thereby preparing a manganese-based positive electrode material with good comprehensive performance and improving the electrochemical performance of the battery.
[0038] (5) The preparation method of the present invention utilizes the existing mature conventional co-precipitation process, and the precursor of the spindle-shaped manganese-based positive electrode material can be prepared without additional changes in the process and equipment. Combined with the conventional sintering process, there is no need to add a solvent and multiple crushing, and a lithium manganese-based positive electrode material with excellent electrochemical properties and stable cycle performance can be obtained. The operation is simple and is conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a SEM image of the precursor of the manganese-based positive electrode material in Example 1.
[0040] Figure 2 This is the SEM image of the precursor of the manganese-based positive electrode material in Comparative Example 1.
[0041] Figure 3 This is the SEM image of the precursor of the manganese-based positive electrode material in Comparative Example 3.
[0042] Figure 4 This is a SEM image of the precursor of the manganese-based positive electrode material in Example 2.
[0043] Figure 5 This is a SEM image of the precursor of the manganese-based positive electrode material in Example 3.
[0044] Figure 6 This is the SEM image of the manganese-based positive electrode material prepared in Example 7.
[0045] Figure 7 This is the SEM image of the manganese-based positive electrode material prepared in Example 8. DETAILED DESCRIPTION
[0046] As mentioned above, in the first aspect, the present invention provides a precursor of a manganese-based positive electrode material, the chemical formula of the precursor of the manganese-based positive electrode material is Ni x Mn y Co 1-x-y (OH)2, wherein: 0.65≤y≤0.9, for example: 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, etc.; 0<x≤0.3, for example: 0.1, 0.15, 0.2, 0.25, 0.3, etc.; its primary particles are spindle-shaped particles.
[0047] The primary particles of the precursor of the manganese-based positive electrode material in the present invention are spindle-shaped, and the spindle particles help to form a manganese-based positive electrode material with a more stable structure during the calcination process, thereby effectively improving the specific capacity and cycle stability of the battery.
[0048] Preferably, the secondary particles of the precursor of the manganese-based positive electrode material are branch-shaped particles composed of spindle-shaped particles interlaced and interconnected.
[0049] The primary particles of the precursor of the manganese-based positive electrode material in the present invention are spindle-shaped, and the spindle-shaped primary particles are cross-interconnected to form a precursor with a special branch structure. The branch-like structure can be used to prepare a manganese-based positive electrode material with a relatively uniform morphology through calcination, thereby improving the electrochemical performance of the positive electrode material.
[0050] Preferably, the D50 of the precursor of the manganese-based positive electrode material is 2~5μm, for example, 2.2μm, 2.4μm, 2.6μm, 2.8μm, 3.0μm, 3.2μm, 3.4μm, 3.6μm, 3.8μm, 4.0μm, 4.2μm, 4.4μm, 4.6μm, 4.8μm, 5.0μm, etc.
[0051] In the second aspect, the present invention provides a method for preparing a precursor of a manganese-based positive electrode material, which is a co-precipitation reaction method, using at least one of carbonate and bicarbonate and hydroxide as a composite precipitant, and using alcohol amine as a crystal directing agent; the composite precipitant solution, alcohol amine solution, metal salt mixed solution and complexing agent solution are subjected to a co-precipitation reaction to prepare a manganese-based positive electrode material precursor.
[0052] In the preparation method of the precursor of the present invention, hydroxide and at least one of carbonate and bicarbonate are used as a composite precipitant, and alcohol amine is added as a crystal directing agent to control the growth mode of the crystal, thereby preparing a precursor of a spindle-shaped manganese-based positive electrode material, thereby preparing a manganese-based positive electrode material with good comprehensive performance and improving the electrochemical performance of the battery.
[0053] Preferably, the hydroxide is one or both of sodium hydroxide and potassium hydroxide; the carbonate is one or both of sodium carbonate and potassium carbonate; and the bicarbonate is one or both of sodium bicarbonate and potassium bicarbonate.
[0054] Preferably, in the composite precipitant, the ratio of the mass of carbonate and bicarbonate to the mass of hydroxide is 1:(20-100), for example 1:100, 1:90, 1:80, 1:70, 1:60, 1:50, 1:40, 1:30, 1:20, etc.; the concentration of the composite precipitant in the composite precipitant solution is 50-300 g / L, for example 50 g / L, 75 g / L, 100 g / L, 125 g / L, 150 g / L, 175 g / L, 200 g / L, 225 g / L, 250 g / L, 275 g / L, 300 g / L, etc.
[0055] Preferably, the alcoholamine is one or more of monoethanolamine, diethanolamine, and triethanolamine. Typical but non-limiting combinations include a combination of monoethanolamine and diethanolamine, a combination of monoethanolamine and triethanolamine, a combination of diethanolamine and triethanolamine, etc.; the concentration of the alcoholamine solution is 0.1-5 g / L, for example, 0.1 g / L, 0.2 g / L, 0.4 g / L, 0.8 g / L, 1 g / L, 2 g / L, 3 g / L, 5 g / L, etc.
[0056] Preferably, the metal salt mixed solution is prepared according to the metal elements and the ratio of the metal elements required in the chemical formula of the precursor of the manganese-based positive electrode material; the concentration of the metal salt in the metal salt mixed solution is 85-115 g / L.
[0057] Preferably, the complexing agent is one or more of ammonia water, ammonium bicarbonate, ammonium sulfate or ammonium oxalate solution. Typical but non-limiting combinations include a combination of ammonia water and ammonium bicarbonate solution, a combination of ammonium bicarbonate solution and ammonium sulfate solution, a combination of ammonia water and ammonium oxalate solution, or a combination of ammonia water, ammonium bicarbonate solution and ammonium oxalate solution, etc. The concentration of the complexing agent solution is 5-40g / L, for example 5g / L, 10g / L, 15g / L, 20g / L, 25g / L, 30g / L, 35g / L, 40g / L, etc.
[0058] Preferably, during the coprecipitation reaction, the pH of the reaction solution is controlled to be 10.0-11.5, for example, 10.0, 10.5, 11 or 11.5.
[0059] Preferably, the stirring speed of the coprecipitation reaction is 500~1000rpm, for example, 500rpm, 550rpm, 600rpm, 650rpm, 700rpm, 750rpm, 800rpm, 850rpm, 900rpm, 950rpm, 1000rpm, etc.
[0060] Preferably, the temperature of the coprecipitation reaction is 45-60°C, for example, 45°C, 48°C, 50°C, 52°C, 55°C, 58°C, 60°C, etc.
[0061] Preferably, a method for preparing a precursor of a manganese-based positive electrode material specifically comprises the following steps: (1) Mix water, precipitant, complexing agent and alcohol amine to prepare the reaction base liquid; (2) A composite precipitant solution, an alcohol amine solution, a metal salt mixed solution, and a complexing agent solution are simultaneously introduced into the reaction base liquid to carry out a co-precipitation reaction; when the precipitate reaches a target particle size, a precursor of a manganese-based positive electrode material is obtained.
[0062] Preferably, in step (1), the precipitant is one or both of sodium hydroxide and potassium hydroxide, and the concentration of the precipitant in the reaction base liquid is 50-300 g / L, for example, 50 g / L, 75 g / L, 100 g / L, 125 g / L, 150 g / L, 175 g / L, 200 g / L, 225 g / L, 250 g / L, 275 g / L, 300 g / L, etc.
[0063] Preferably, in step (1), the concentration of the alcoholamine in the reaction base solution is 0.1-2 g / L, for example: 0.1 g / L, 0.3 g / L, 0.5 g / L, 0.7 g / L, 0.9 g / L, 1.1 g / L, 1.3 g / L, 1.5 g / L, 1.7 g / L, 1.9 g / L, 2.0 g / L, etc.
[0064] Preferably, in step (1), the complexing agent is one or more of ammonia water, ammonium bicarbonate, ammonium sulfate or ammonium oxalate solution; the concentration of the complexing agent in the reaction base solution is 1-10 g / L, 1 g / L, 2 g / L, 4 g / L, 5 g / L, 6 g / L, 8 g / L, 10 g / L, etc.
[0065] Preferably, in step (1), the pH of the reaction base solution is 11-13, for example, 11, 11.2, 11.4, 11.6, 11.8, 12, 12.2, 12.4, 12.6, 12.8, 13, etc.
[0066] Preferably, in step (2), the target particle size is 2-5 μm, for example, 2.0 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3.0 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, 4.0 μm, 4.2 μm, 4.4 μm, 4.6 μm, 4.8 μm, 5.0 μm, etc.
[0067] Preferably, in step (2), after the coprecipitation reaction, the step further includes filtration, washing and drying.
[0068] Preferably, the drying temperature is 80-130°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, etc.
[0069] In a third aspect, the present invention provides a manganese-based positive electrode material, wherein the manganese-based positive electrode material is prepared from a precursor of the aforementioned manganese-based positive electrode material.
[0070] Preferably, the manganese-based positive electrode material is a quasi-single crystal manganese-based positive electrode material.
[0071] The manganese-based positive electrode material in the present application is a quasi-single crystal manganese-based positive electrode material, which has a higher load voltage, better safety performance and cycle performance, and smaller interface side reactions compared to polycrystalline materials.
[0072] The precursor of the manganese-based positive electrode material in the present invention does not require any auxiliary agent or special treatment, and a single-crystal-like manganese-based positive electrode material with uniform morphology and stable structure can be prepared by calcination.
[0073] In a fourth aspect, the present invention provides a method for preparing a manganese-based positive electrode material, comprising the following steps: The precursor of the manganese-based positive electrode material is mixed with a lithium source and then calcined in an oxygen-containing atmosphere to obtain the manganese-based positive electrode material.
[0074] Preferably, the lithium source is one or both of lithium carbonate and lithium oxide, and the molar ratio of the precursor of the manganese-based positive electrode material to the lithium in the lithium source is 1:(1.3-1.5), for example: 1:1.3, 1:1.4, 1:1.5, etc.
[0075] Preferably, the oxygen-containing atmosphere is an oxygen atmosphere or an air atmosphere.
[0076] Preferably, the calcination temperature is 850-1000°C, for example, 850°C, 875°C, 900°C, 925°C, 950°C, 975°C, 1000°C, etc.; the calcination time is not less than 8h, for example, 8h, 10h, 12h, 14h, 15h, 20h, etc.
[0077] In a fifth aspect, the present invention provides a lithium-ion battery comprising the aforementioned manganese-based positive electrode material.
[0078] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.
[0079] Example 1 The method for preparing the precursor of the manganese-based positive electrode material in this embodiment includes the following steps: (1) Water, an aqueous ammonia solution with a mass concentration of 30 g / L, an aqueous sodium hydroxide solution with a mass concentration of 200 g / L, and an aqueous diethanolamine solution with a mass concentration of 2 g / L were mixed to obtain a reaction base solution with a pH of 12, an aqueous ammonia concentration of 4 g / L, and a diethanolamine concentration of 0.2 g / L.
[0080] (2) A nickel-cobalt-manganese sulfate solution (Ni:Co:Mn molar ratio is 10:10:80) with a mass concentration of 85 g / L, ammonia water with a mass concentration of 30 g / L, a composite precipitant aqueous solution with a mass concentration of 200 g / L (the composite precipitant is composed of sodium carbonate and sodium hydroxide, and the mass ratio of sodium carbonate to sodium hydroxide is 1:30) and a diethanolamine aqueous solution (crystal directing agent) with a mass concentration of 2 g / L are simultaneously added to the reaction base liquid obtained in step (1) by a peristaltic pump, and a coprecipitation reaction is carried out at 57° C., the pH of the coprecipitation reaction is controlled to be 10-11.0, and the stirring speed of the coprecipitation reaction is controlled to be 800 rpm; when the coprecipitation reaction reaches D50 of 3 μm, the feeding is stopped, the reaction solution is filtered, and then washed with sodium hydroxide solution and hot water in turn, and the filter cake is dried at 100° C. to obtain Ni, a precursor of the manganese-based positive electrode material. 0.1 Mn 0.8 Co 0.1 (OH)2.
[0081] The SEM image of the precursor of the manganese-based positive electrode material prepared in this embodiment is as follows: Figure 1 As shown, the primary particles of the precursor are spindle-shaped, and the spindle-shaped primary particles are cross-interconnected to form a special branch-shaped precursor.
[0082] Comparative Example 1 The method is basically the same as Example 1, except that in step (2), no composite precipitant is used, and 200 g / L sodium hydroxide is used as the precipitant.
[0083] The SEM image of the manganese-based positive electrode material precursor prepared in this comparative example is as follows Figure 2 As shown, the primary particles of the precursor are in the form of flakes, and the flake-shaped primary particles are accumulated to form spherical secondary particles.
[0084] Comparative Example 2 It is basically the same as Example 1, except that: In step (1), sodium hydroxide is replaced by sodium carbonate of equal concentration in the reaction base liquid.
[0085] In step (2), no composite precipitant is used, and 200 g / L sodium carbonate is used as a precipitant during the reaction.
[0086] The microscopic morphology of the precursor of the manganese-based positive electrode material prepared in this comparative example is that the primary particles are flaky, and the flaky primary particles are accumulated to form spherical secondary particles.
[0087] Comparative Example 3 The process is basically the same as Example 1, except that in step (2), no diethanolamine crystal directing agent solution is added.
[0088] The SEM image of the lithium-rich manganese-based positive electrode material precursor prepared in this comparative example is as follows Figure 3 As shown, the primary particles of the precursor are in the form of thin flakes, and the thin flake-shaped primary particles are accumulated into spherical secondary particles.
[0089] Example 2 The method is basically the same as Example 1, except that in step (2), the mass ratio of sodium carbonate to sodium hydroxide is 1:100.
[0090] The SEM image of the precursor of the manganese-based positive electrode material prepared in this embodiment is as follows: Figure 4 As shown, the primary particles of the precursor are spindle-shaped, and the spindle-shaped primary particles are cross-interconnected to form a special branch-shaped precursor.
[0091] Example 3 The method is basically the same as Example 1, except that in step (2), the mass ratio of sodium carbonate to sodium hydroxide is 1:20.
[0092] The SEM image of the precursor of the manganese-based positive electrode material prepared in this embodiment is as follows: Figure 5 As shown, the primary particles of the precursor are spindle-shaped, and the spindle-shaped primary particles are cross-interconnected to form a special branch-shaped precursor.
[0093] Example 4 The method for preparing the precursor of the manganese-based positive electrode material in this embodiment includes the following steps: (1) Water, an ammonium sulfate solution with a mass concentration of 20 g / L, a sodium hydroxide solution with a mass concentration of 220 g / L, and a monoethanolamine solution with a mass concentration of 1 g / L are mixed to obtain a reaction base solution with a pH of 12.5, an ammonium sulfate solution of 6 g / L, and a monoethanolamine concentration of 0.2 g / L.
[0094] (2) A nickel-cobalt-manganese sulfate solution with a mass concentration of 96 g / L (a molar ratio of Ni:Co:Mn is 15:10:75), an ammonium sulfate solution with a mass concentration of 20 g / L, a composite precipitant solution with a mass concentration of 220 g / L (the composite precipitant is composed of sodium carbonate and sodium hydroxide, and the mass ratio of sodium carbonate to sodium hydroxide is 1:75) and a monoethanolamine crystal directing agent solution with a mass concentration of 1 g / L are simultaneously added to the reaction base liquid obtained in step (1) by a peristaltic pump, and a coprecipitation reaction is carried out at 60° C. The pH of the coprecipitation reaction is controlled to be 10.5-11.5, and the stirring speed of the coprecipitation reaction is controlled to be 700 rpm; when the coprecipitation reaction is performed until D50 reaches 3.5 μm, the feeding is stopped, the reaction solution is filtered, and then washed with sodium hydroxide solution and hot water in turn, and the filter cake is dried at 110° C. to obtain a single-crystal-type lithium-rich manganese-based positive electrode material precursor Ni 0.15 Mn 0.75 Co 0.1 (OH)2.
[0095] The precursor Ni of the manganese-based positive electrode material prepared in this embodiment 0.15 Mn 0.75 Co 0.1 The primary particles of (OH)2 are spindle-shaped, and the spindle-shaped primary particles are cross-interconnected to form special branch-shaped precursors.
[0096] Example 5 The method for preparing the precursor of the manganese-based positive electrode material in this embodiment includes the following steps: (1) Water, an aqueous solution of ammonium oxalate having a mass concentration of 40 g / L, an aqueous solution of sodium hydroxide having a mass concentration of 180 g / L, and an aqueous solution of triethanolamine having a mass concentration of 4.0 g / L were mixed to obtain a reaction base solution having a pH of 12.3, an ammonium oxalate concentration of 5.5 g / L, and a triethanolamine concentration of 0.5 g / L.
[0097] (2) A nickel-cobalt-manganese sulfate solution (Ni:Co:Mn molar ratio is 15:15:70) with a mass concentration of 115 g / L, an ammonium oxalate aqueous solution with a mass concentration of 40 g / L, a composite precipitant aqueous solution (the composite precipitant is composed of sodium bicarbonate and potassium hydroxide, and the mass ratio of sodium bicarbonate to potassium hydroxide is 1:55) with a mass concentration of 180 g / L, and a triethanolamine aqueous solution (crystal directing agent) with a mass concentration of 4.0 g / L are simultaneously added to the reaction base liquid obtained in step (1) by a peristaltic pump, and a coprecipitation reaction is carried out at 45° C., the pH of the coprecipitation reaction is controlled to be 10.0-11.0, and the stirring speed of the coprecipitation reaction is controlled to be 1000 rpm; when the coprecipitation reaction reaches the target particle size of 4.5 μm, the feeding is stopped, the reaction solution is filtered, and then washed with sodium hydroxide solution and hot water in turn, and the filter cake is dried at 120° C. to obtain a single-crystal-type lithium-rich manganese-based positive electrode material precursor Ni 0.15 Mn 0.7 Co 0.15 (OH)2.
[0098] The precursor Ni of the manganese-based positive electrode material prepared in this embodiment 0.15 Mn 0.7 Co 0.15 The (OH)2 primary particles are spindle-shaped, and the spindle-shaped primary particles are cross-interconnected to form special branch-shaped precursors.
[0099] Example 6 The method for preparing the precursor of the manganese-based positive electrode material in this embodiment includes the following steps: (1) Water, an aqueous ammonia solution with a mass concentration of 30 g / L, an aqueous sodium hydroxide solution with a mass concentration of 130 g / L, and an aqueous triethanolamine solution with a mass concentration of 1.5 g / L were mixed to obtain a reaction base solution with a pH of 12, an aqueous ammonia concentration of 10.0 g / L, and a triethanolamine concentration of 0.3 g / L.
[0100] (2) A nickel-cobalt-manganese sulfate solution (Ni:Co:Mn molar ratio is 20:10:70) with a mass concentration of 100 g / L, an ammonia solution with a mass concentration of 15 g / L, a composite precipitant aqueous solution with a mass concentration of 130 g / L (the composite precipitant is composed of sodium bicarbonate and potassium hydroxide, and the mass ratio of sodium bicarbonate to potassium hydroxide is 1:80) and a triethanolamine crystal aqueous solution (crystal directing agent) with a mass concentration of 1.5 g / L are simultaneously added to the reaction base liquid obtained in step (1) by a peristaltic pump, and a coprecipitation reaction is carried out at 55° C., the pH of the coprecipitation reaction is controlled to be 10.0-11.0, and the stirring speed of the coprecipitation reaction is controlled to be 1000 rpm; when the coprecipitation reaction reaches D50 of 2.5 μm, the feeding is stopped, the reaction solution is filtered, and then washed with sodium hydroxide solution and hot water in turn, and the filter cake is dried at 120° C. to obtain a single-crystal-type lithium-rich manganese-based positive electrode material precursor Ni 0.2 Mn 0.7 Co 0.1 (OH)2.
[0101] The precursor Ni of the manganese-based positive electrode material prepared in this embodiment 0.2 Mn 0.7 Co 0.1 The (OH)2 primary particles are spindle-shaped, and the spindle-shaped primary particles are cross-interconnected to form special branch-shaped precursors.
[0102] Example 7 Preparation of manganese-based positive electrode material: Ni 0.1 Mn 0.8 Co 0.1 After (OH)2 and lithium carbonate are evenly mixed (the precursor and lithium in lithium carbonate are added at a molar ratio of 1:1.5), they are sintered at 950°C in an air atmosphere for 16 hours to obtain the manganese-based positive electrode material Li 1.2 Ni 0.08 Mn 0.64 Co 0.08 O2.
[0103] In this example, the manganese-based positive electrode material Li 1.2 Ni 0.08 Mn 0.64 Co 0.08 The SEM image of O2 is as follows Figure 6 As shown, the microstructure of the positive electrode material is a single crystal nodule-like structure with regular particle shape and relatively uniform size.
[0104] Comparative Example 4 It is basically the same as Example 7, except that the precursor of the manganese-based positive electrode material is prepared in Example 1.
[0105] The manganese-based positive electrode material Li prepared in this comparative example 1.2 Ni 0.08 Mn 0.64 Co 0.08 The SEM image of O2 is as follows Figure 7 As shown, the positive electrode material is a spherical secondary particle with a polycrystalline structure composed of strip-shaped primary particles.
[0106] Comparative Example 5 It is basically the same as Example 7, except that the precursor of the manganese-based positive electrode material is prepared in Example 2.
[0107] The manganese-based positive electrode material Li prepared in this comparative example 1.2 Ni 0.08 Mn 0.64 Co 0.08 O2 has a polymorphic crystal structure.
[0108] Comparative Example 6 It is basically the same as Example 7, except that the precursor of the manganese-based positive electrode material is prepared in Example 3.
[0109] The manganese-based positive electrode material Li prepared in this comparative example 1.2 Ni 0.08 Mn 0.64 Co 0.08 O2 has a polymorphic crystal structure.
[0110] Example 8 It is basically the same as Example 7, except that the precursor of the manganese-based positive electrode material is prepared in Example 2.
[0111] In this example, the manganese-based positive electrode material Li 1.2 Ni 0.08 Mn 0.64 Co 0.08 O2 has a single-crystal structure.
[0112] Example 9 Basically the same as Example 7, except that the precursor of the manganese-based positive electrode material is prepared in Example 3.
[0113] In this example, the manganese-based positive electrode material Li 1.2 Ni 0.08 Mn 0.64 Co 0.08 O2 has a single-crystal structure.
[0114] Example 10 Preparation of manganese-based positive electrode material: Ni 0..15 Mn 0.75 Co 0.1After (OH)2 and lithium carbonate are evenly mixed (the precursor and lithium in lithium carbonate are added at a molar ratio of 1:1.3), they are sintered at 1000°C in an air atmosphere for 10 hours to obtain the manganese-based positive electrode material Li 1.2 Ni 0.12 Mn 0.6 Co 0.08 O2, which is a single-crystal-like crystal structure.
[0115] Embodiment 11 Preparation of manganese-based positive electrode material: Ni 0.15 Mn 0.7 Co 0.15 After (OH)2 and lithium carbonate are evenly mixed (the precursor and lithium in lithium carbonate are added at a molar ratio of 1:1.4), they are sintered at 850°C in an air atmosphere for 24 hours to obtain the manganese-based positive electrode material Li 1.5 Ni 0.128 Mn 0.6 Co 0.128 O2, which is a single-crystal-like crystal structure.
[0116] Example 12 Preparation of manganese-based positive electrode material: Ni 0.2 Mn 0.7 Co 0.1 After (OH)2 and lithium carbonate are evenly mixed (the precursor and lithium in lithium carbonate are added at a molar ratio of 1:1.4), they are sintered at 900°C in an air atmosphere for 18 hours to obtain the manganese-based positive electrode material Li 1.2 Ni 0.16 Mn 0.56 Co 0.08 O2, which is a single-crystal-like crystal structure.
[0117] The battery assembly is completed by: The manganese-based positive electrode materials obtained in Examples 7 to 12 and Comparative Examples 4 to 6 were assembled into lithium-ion button batteries according to the following method: the manganese-based positive electrode material, the binder polyvinylidene fluoride and the conductive agent Super P were added to N-methylpyrrolidone in a mass ratio of 80:10:10 and stirred to form a positive electrode slurry; the positive electrode slurry was then evenly coated on the positive electrode collector aluminum foil, and the positive electrode sheet was obtained after drying and rolling; a lithium sheet was selected as the negative electrode and a porous polypropylene film was used as the separator, and the obtained positive electrode sheet, negative electrode and separator were stacked to form a battery cell, and an electrolyte was injected into the battery cell to obtain a lithium-ion button battery.
[0118] The specific capacity and cycle capacity retention rate of the obtained lithium ion button battery were tested. The method for testing the specific capacity is as follows: using a blue battery test system, at 25°C, the lithium ion battery is charged and discharged three times in a voltage range of 2V to 4.6V with a charge and discharge mode of 0.1C (1C=250 mAh / g), and the battery specific capacity is measured. The initial discharge specific capacity at 0.1C is shown in Table 1; the method for testing the capacity retention rate is as follows: the voltage range of the button battery for charge and discharge is 2.0 to 4.6V, and before the cycle test, a smaller current density of 0.1C is used for three activations, and at 25°C, the battery is cycled with a charge and discharge mode of a current density of 0.1C. After 100 cycles, the discharge capacity of the battery at this time is divided by the discharge capacity of the first cycle, which is the 100-cycle cycle capacity retention rate of the battery. The capacity retention rates after 50 and 100 cycles are shown in Table 1.
[0119] Table 1 It can be seen from the data in Table 1 that the manganese-based positive electrode material prepared in Example 7 is a quasi-single crystal manganese-based positive electrode material, and the specific capacity and cycle stability of the corresponding assembled battery are improved to a certain extent compared with the polymorphs in Comparative Examples 4 to 6. The manganese-based positive electrode materials prepared in Examples 7 to 12 are all quasi-single crystal manganese-based positive electrode materials. Due to the adjustment of process parameters, the specific capacity and cycle stability of the assembled battery will fluctuate to a certain extent.
[0120] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A precursor of a manganese-based positive electrode material, characterized in that: The chemical formula of the precursor of the manganese-based positive electrode material is Ni x Mn y Co 1-x-y (OH)2, wherein: 0.65≤y≤0.9, 0<x≤0.3; its primary particles are spindle-shaped particles.
2. The precursor of the manganese-based positive electrode material according to claim 1, characterized in that: The secondary particles of the precursor of the manganese-based positive electrode material are branch-shaped particles formed by interlaced and interconnected spindle-shaped particles.
3. The precursor of the manganese-based positive electrode material according to claim 1, characterized in that: The D50 of the precursor of the manganese-based positive electrode material is 2-5 μm.
4. A method for preparing a precursor of a manganese-based positive electrode material according to any one of claims 1 to 3, characterized in that: The method is a co-precipitation reaction method, using at least one of carbonate and bicarbonate and hydroxide as a composite precipitant, and using alcohol amine as a crystal directing agent; the composite precipitant solution, alcohol amine solution, metal salt mixed solution and complexing agent solution are subjected to a co-precipitation reaction to prepare a precursor of a manganese-based positive electrode material.
5. The method for preparing a precursor of a manganese-based positive electrode material according to claim 4, characterized in that: The hydroxide is one or both of sodium hydroxide and potassium hydroxide; the carbonate is one or both of sodium carbonate and potassium carbonate; the bicarbonate is one or both of sodium bicarbonate and potassium bicarbonate; In the composite precipitant, the mass ratio of carbonate and bicarbonate to the mass ratio of hydroxide is 1:(20-100); the concentration of the composite precipitant in the composite precipitant solution is 50-300 g / L; The alcoholamine is one or more of monoethanolamine, diethanolamine and triethanolamine; the concentration of the alcoholamine solution is 0.1-5 g / L.
6. The method for preparing a precursor of a manganese-based positive electrode material according to claim 4, characterized in that: The metal salt mixed solution is prepared according to the metal elements and the ratio of the metal elements required in the chemical formula of the precursor of the manganese-based positive electrode material; the concentration of the metal salt in the metal salt mixed solution is 85-115 g / L; The complexing agent is one or more of ammonia water, ammonium bicarbonate, ammonium sulfate or ammonium oxalate solution; the concentration of the complexing agent solution is 5-40g / L.
7. The method for preparing a precursor of a manganese-based positive electrode material according to claim 4, characterized in that: During the coprecipitation reaction, the pH of the reaction system is controlled to be 10.0-11.
5.
8. A manganese-based positive electrode material, characterized in that: The manganese-based positive electrode material is prepared from a precursor of the manganese-based positive electrode material according to any one of claims 1 to 3, or a precursor of the manganese-based positive electrode material prepared by the preparation method according to any one of claims 4 to 7.
9. The manganese-based positive electrode material according to claim 8, characterized in that: The manganese-based positive electrode material is a quasi-single crystal manganese-based positive electrode material.
10. A lithium ion battery, characterized in that: Comprising the manganese-based positive electrode material as described in claim 8 or 9.